2014
DOI: 10.1007/s13369-014-1300-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of One-Dimensional Inviscid and Two-Dimensional Viscous Flows Using Entropy Preserving Method

Abstract: In this paper, the entropy preserving (EP) scheme (which is introduced recently by Jameson) has been considered deeply and compared with the other artificial viscosity and upwind schemes. The discretization of the governing equations in the EP scheme is performed in such a way that the entropy is conserved in all those points with no shock. The purpose of this study was to introduce a stable numerical method that enters a minimum artificial dissipation only in the vicinity of shocks. In this paper, an inviscid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Previous works by the authors show that the kinetic energy-preserving (KEP) method leads to the same results as the other methods until the number of grids is low [5]. The challenge is to improve the KEP method to gain better results at low points of the grid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works by the authors show that the kinetic energy-preserving (KEP) method leads to the same results as the other methods until the number of grids is low [5]. The challenge is to improve the KEP method to gain better results at low points of the grid.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Chandrashekar [15,16], Kok [17], and Yan and Jin [18] scrutinized this method in their articles. Also, Javadi and Pasandideh-Fard [5] have applied the KEP method in a onedimensional inviscid convergent-divergent nuzzle flow, two-dimensional inviscid flow over a bump, and two-dimensional viscous flow over a NACA 0012 airfoil. It was shown that the KEP scheme is more accurate if the number of mesh points is increased; and, in contrast to other schemes, there is no limit in increasing the grid points.…”
Section: Introductionmentioning
confidence: 99%